The Effect of Leadership Style, Organizational Culture, and Organizational Commitment on Employee Performance at the East Kalimantan Provincial Transportation Department - Dian Kurniasih; Cathas Teguh Prakoso; Hariati Hariati (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyse the influence of leadership style, organisational culture, and organisational commitment on employee performance at the East Kalimantan Provincial Transport Agency, both partially and simultaneously. The study employs a quantitative approach with an explanatory research design. The sample was determined using the Slovin formula via proportionate stratified random sampling, resulting in a total of 104 respondents. Data collection was carried out by distributing questionnaires using a Likert scale. The research data was then transformed into an interval scale using the Method of Successive Intervals (MSI) and analysed using multiple linear regression with the aid of SPSS software. The results of the study indicate that, when considered individually, leadership style does not have a significant effect on employee performance. Meanwhile, organisational culture and organisational commitment have a positive and significant effect on employee performance. Collectively, leadership style, organisational culture, and organisational commitment have a significant effect on employee performance. The results of the regression analysis indicate that organisational commitment is the most dominant variable influencing employee performance, followed by organisational culture, whilst leadership style has not yet exerted an optimal influence. Consequently, improvements in employee performance are more strongly influenced by high levels of organisational commitment and a conducive organisational culture.